Rapid enzymatic detection of organophosphorous and carbamate pesticides in water - Mwila, Katayi (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2012)
The increased use of pesticides has resulted in a corresponding increase in concern for the effect they may have on the health of humans and other non-target organisms. The two main areas of concern are the toxicological effects that mixtures of pesticides may have as well as the endocrine disrupting effects. Although the individual pesticides may be present at concentrations below the levels deemed to be detrimental to health, it has been argued that their combined effect may still result in elevated health risks. Another important aspect of pesticide risk assessment requires a consideration of the breakdown products of pesticides and their effect on human health. There has been very little research into the effects of degradation products and this issue should be addressed as these could potentially pose a higher risk than their parent compounds. One of the most important bio-markers available for use is the ubiquitous enzyme acetylcholinesterase (AChE). This enzyme is responsible for one of the most important functions in the body; namely nerve impulse transmission, upon which all life depends. The inhibition of this enzyme indicates toxicity and as a subsequence, a threat to the organism's well-being. Bioassays have also recently been developed to test chemicals for endocrine disrupting effects. These tests rely on a dose response equivalent to that of the most potent well known estrogen 17-Î² estradiol. Any chemical that has a measurable response is deemed to display endocrine disrupting effects. This first aim of this study was to investigate the toxicological and endocrine disrupting effects of three organophosphorus pesticides; aldicarb, parathion and demeton-S-methyl, in addition to two breakdown products; aminophenol and p-nitrophenol. Two carbamate pesticides; carbaryl and carbofuran were also analysed. The toxicological effects of mixtures of the parent pesticide compounds were tested to assess if any antagonistic, additive or synergistic effects were observed. This data was then used in conjunction with an artificial neural network to assess if individual pesticides could be distinguished from mixtures of pesticides. A final objective was to sample various Eastern Cape water sources, utilising the enzymatic assay to determine the presence of any of these pesticides in these samples. There were several conclusions drawn from this study. AChE was successfully used as an assay to test the toxicity of the pesticides under investigation, based on their inhibition of this enzyme. An important factor for consideration throughout the study was the need to establish basal and monitor AChE activity (i.e. the need to monitor AChE activity in the absence of any pesticide). This ensured accurate comparison of the results obtained. It was found that demeton-S-methyl was the most potent of these pesticides followed by carbaryl, parathion, aldicarb and finally carbofuran, and that carbofuran could potentiate AChE. The results indicated that pesticide mixtures generally exhibited an additive inhibitory effect on AChE, although at some concentrations of pesticides, synergistic and antagonistic effects were noted. From the data using mixtures of pesticides, a feed forward neural network was created that was successfully able to distinguish individual pesticides from mixtures within its training parameters. None of the pesticides tested displayed endocrine disrupting properties in the Yeast Estrogen Screen (YES), T47D-KBluc and MDA-kb2 bio-assays. Other studies reported mixed results in this regard and thus no final conclusions could be drawn. The Blaauwkrantz River, Kariega River, Sundays River, Swartkops River and Kowie River were all tested for pesticides and although positive results were recorded, conventional methods indicated that there were no pesticides in the rivers. There were, however, trace metals present which are known to inhibit AChE, thus causing a false positive result. These results indicated that AChE can be used as a high throughput initial pre-screening tool, but that it cannot serve as a substitute for more accurate conventional testing methods.
Keywords: Organophosphorus compounds; Carbamates; Water -- Pesticide content -- South Africa -- Eastern Cape; Water quality biological assessment -- South Africa -- Eastern Cape; Water quality management -- South Africa -- Eastern Cape; Pesticides -- Toxicology -- South Africa -- Eastern Cape; Biological assay; Acetylcholinesterase; Parathion; Aldicarb; Carbaryl; Carbofuran; Nitrophenols